ХАЛЫҚАРАЛЫҚ МӘДЕНИЯТТЫҢ ТҮРЛЕРИ, ДҮЗИЛИСИ ҲӘМ МАЗМУНЫ ҲАҚҚЫНДА - Әлеуов, Ө. (ILIM hám JÁMIYET, 2021)
The article deals with the forms, content, structure of interethnic communication, which represents social and personal relations of various nations, more over it exchanches both material and spiritual heritages, and also with views, feelings, emotions in the process of social and every day life activities.